Augmented reality as a tool for teaching of the automotive electrical and electronic systems formative module - Méndez García, Lennin Patricio; Herrera Granda, Israel David (SATHIRI, 2025)
The difficulty in learning of the Automotive Electrical and Electronic Systems training module by the students from the Third Technical Baccalaureate in Automotive Electromechanics, leads to the present research has as the aim to implement the use of Augmented Reality (AR) in the process of teaching. The applied research was documental, field, and quasi-experimental type, with a mixed approach. A pre-test was engaged to 38 students from two parallels of the General Julio Andrade Educational Unit, located in the province of Carchi (Ecuador), to identify the prior knowledge, and a post-test after of using AR to know the level of acquired learning. With the development of the established proposal, an improvement in academic performance was evident, and it was reflected on the obtained result in the post-test in the students of parallel B with an average of 8,50/10 points, unlike the score from the parallel A, in which the traditional methodology was applied, and 7,78/10 points were gained. As a conclusion, the application of the technological tool of AR is feasible and generates in the students a high interest of learning in the aforementioned module.